The importance of nurses in liver transplant centers - Genova, Francielen Cristina Lopes; Tonelli, Silvia Ricci (Brazilian Journal of Transplantation, 2016)
Purpose: Liver transplantation is a complex procedure performed in large hospitals demanding a complete hospital infrastructure and a highly trained multidisciplinary team due to functional changes throughout the body. From such information the aim was to achieve a synthesis and discussion of scientific publications on the actions of the nurse for patients on the waiting list for liver transplantation, indicating the main pathologies leading to transplant, nursing care actions implemented patient in the queue, addressing social, physical and psychosocial issues and describing the preparation of preoperatively care aiming better outcomes in patients to be transplanted. This literature review was prepared by covering books, papers, magazines and government sites in the following databases: LILACS, SciELO and PubMed published from 2005 to 2015. From 40 articles, nine were selected related to the proposed theme. It was concluded that the nurse in transplanters units is responsible by managing the care, welfare, administrative, teaching and research activities, and the need to create protocols and manuals to clarify to patients any questions related tothe process, in an early action to generate good post-surgery results.